Friedrich Nietzsche and the Politics of the Soul : A Study of Heroic Individualism - Thiele, Leslie Paul (Book collections on Project MUSE., 1990)
Leslie Thiele presents an original and accessible essay on the great thinker's attempt to lead a heroic life as a philosopher, artist, saint, educator, and solitary. He takes as his point of departure Nietzsche's conception of the soul as a multiplicity of conflicting drives and personae, and focuses on the task Nietzsche allotted himself "to make a cosmos out of his chaotic inheritance." This struggle to "become what you are" by way of a spiritual politics is demonstrated to be Nietzsche's foremost concern, which fused his philosophy with his life.